REDESIGNING VISUAL IDENTITY AND ITS APLICATION FOR MEDIA PROMOTION OF KAWISTA DEWA BURUNG AS A GIFT ORINIGALLY FROM REMBANG - Bakhtiar, Aziz (Jurusan Seni Rupa Fakultas Bahasa dan Seni, 2018)
Theprocess of designing the visual identity and its application on the promotion media was using elements and design principles to produce a good design.This redesigning activity is done because there is still public ignorance about Kawista Dewa Burung which is a typical souvenir of Rembang since 1925. This redesigning activity include redesigning visual identity in the form of logo, and tagline design and also packaging design. While the design of promotional media Kawista Dewa Burung include advertising campaigns in the form of billboard design, flyers, signposts, nameplate outlets, x-banner, and also social media pack. Sales promotion (sales promotion) with the application of merchandise design. Public relations (public relations) in the form of stationary set design. Hope from redesign The visual identity of Kawista God of Birds can help create brand awareness in target market mind. The selected media in redesigning the visual identity of Kawista God Bird is tailored to the target market so that the design is not wasted.